2018
DOI: 10.5301/tj.5000612
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging in evaluating the efficacy of concurrent chemoradiotherapy in the treatment of non-small cell lung cancer

Abstract: Tumori 2017; 00(00): 000-000 ORIGINAL RESEARCH ARTICLEcountries, although it is decreasing in developed countries. In addition to smoking, sex, nationality, and histology also account for NSCLC (3)(4)(5). Despite advances in standard treatment and early detection, NSCLC is often diagnosed at an advanced stage. Patients typically have poor prognosis, with a 5-year survival rate of less than 15% (6). Concurrent chemoradiotherapy (CCRT) is a new model developed in recent decades. A clinical study reported that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…This may be due to the cytotoxic effect of chemotherapeutic drugs destroying the integrity of tumor cells, increasing intracellular necrosis, inducing tumor cell apoptosis, or directly killing tumor cells, resulting in decreased cell density and increased water molecule diffusion movement after effective chemotherapy. The results for ADC were the same with previous studies 3–7 in patients with primary and recurrent lung tumors. Theoretically, the D value is more representative of the water molecular diffusion than ADC because of the separation of water molecule diffusion and microcirculation perfusion.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This may be due to the cytotoxic effect of chemotherapeutic drugs destroying the integrity of tumor cells, increasing intracellular necrosis, inducing tumor cell apoptosis, or directly killing tumor cells, resulting in decreased cell density and increased water molecule diffusion movement after effective chemotherapy. The results for ADC were the same with previous studies 3–7 in patients with primary and recurrent lung tumors. Theoretically, the D value is more representative of the water molecular diffusion than ADC because of the separation of water molecule diffusion and microcirculation perfusion.…”
Section: Discussionsupporting
confidence: 87%
“…The reason for this was likely the low cell density or the existence of minor cystoid variation and necrosis, which are less sensitive to chemotherapy because of hypoxia and acidosis. The findings were the same as the results obtained for ADC in lung cancer 6,10,13 and for D in nasopharyngeal carcinoma [29][30][31] and rectal cancer 26,38 but different from the results obtained in other studies. 27,28,32,33 The contradictory results may be due to the diverse research objectives, the heterogeneous scanning and postprocessing techniques, and the different evaluation criteria.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Recently, an interesting article by Xu and colleagues (1) reported on the usefulness of diffusion-weighted magnetic resonance imaging (MRI) in evaluating patients with non-small-cell lung cancer treated with concurrent chemoradiotherapy. In a large cohort of 192 patients, by measuring the apparent diffusion coefficient (ADC) on parametric ADC maps, the authors found that quantitative diffusion-weighted MRI has predictive value in evaluating the short-term efficacy of concurrent chemoradiotherapy.…”
mentioning
confidence: 99%